Slow-release temperature-controlled antifouling agent microsphere as well as preparation method and application thereof

The preparation of sustained-release antifouling microspheres through materials such as sodium alginate, copper pyridinthione and chitosan has solved the problem of difficult to adjust the release rate of antifouling agents, achieved the need for sustained-release effect and temperature-regulated release rate, improved the embedding rate and drug loading, and was environmentally friendly and safe.

CN119563649APending Publication Date: 2025-03-07INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411582087.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, the release rate of antifoulants is difficult to adjust, resulting in the release too fast in a short period of time, and the inability to effectively protect marine biological pollution. The sea water temperatures in different sea areas and seasons are different, making it difficult to meet the demand for temperature-regulating the release rate.

Method used

Sustained-release antifouling agent microspheres were prepared by materials such as sodium alginate, copper pyridylthione and chitosan. The cross-linking of sodium alginate and calcium ions and the anionic cross-linking of sodium alginate and chitosan were constructed to form a bilayer drug-loading structure, and the cross-linking of glutaraldehyde and chitosan were cured to form a stable microsphere structure.

Benefits of technology

It realizes the sustained release effect of antifouling agent, extends the antifouling time, reduces the release rate of copper ions, adapts to the release characteristics of different seawater temperatures, improves the embedding rate and drug loading, reduces the amount of antifouling agent, and has the characteristics of environmental protection and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563649A_ABST
    Figure CN119563649A_ABST
Patent Text Reader

Abstract

The invention discloses a slow-release temperature-controlled antifouling agent microsphere and a preparation method and application thereof, the method comprises the following steps: (1) mixing sodium alginate, copper pyrithione and a CaCl2 solution for reaction, freeze-drying, grinding and crushing to prepare intermediate product particles; and (2) mixing the intermediate product particles in the step (1) with a chitosan solution for reaction, then adding a glutaraldehyde solution for continuous reaction, and freeze-drying to obtain the antifouling agent microspheres. The sodium alginate and chitosan double-crosslinking preparation method adopted by the invention is novel, a double-layer drug-loading structure is constructed by virtue of the crosslinking effect of sodium alginate and calcium ions and the electrostatic interaction between anions and cations of sodium alginate and chitosan, and the thought is novel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine antifouling, and specifically relates to a slow-release temperature-controlled antifouling agent microsphere and a preparation method and application thereof. Background Art

[0002] Marine fouling is an inevitable problem in the process of ship navigation. Microbial fouling on the surface of the hull will directly lead to increased ship resistance and reduced sailing speed, which will greatly increase fuel consumption. It will also cause damage to the hull coating, destroy the hull structure, promote surface aging, damage facilities, cause safety problems and increase resistance, resulting in high fuel consumption and extremely high maintenance costs. Therefore, protection against marine fouling is imperative. Antifouling coatings that prevent and control marine biological fouling mainly rely on the stable release of antifouling agents from the coating to achieve an antifouling effect. Commonly used antifouling agents often contain metal ions such as copper and zinc ions, but using ordinary methods to directly place antifouling agents in the coating will result in a sudden release of antifouling agents, that is, the release rate is very fast in a short period of time, which is difficult to achieve a long-term antifouling effect; and the seawater temperature in different sea areas and seasons is different, and the activity of marine organisms is different. There is an urgent need for an antifouling agent that can adjust the release rate with temperature.

[0003] In the prior art, composite coacervation, in-situ polymerization and ion gelation are often used to prepare coated microspheres:

[0004] 1. Gelatin-arabic gum / urea-formaldehyde resin microcapsules encapsulating DCOIT by complex coacervation and in-situ polymerization (Liu Huatong. Study on PVP-modified silicone coating containing DCOIT sustained-release capsules [D]. Shandong University, 2023. DOI: 10.27272 / d.cnki.gshdu.2023.002207.), the preparation process is as follows:

[0005] Using antifouling agent DCOIT (i.e., isothiazolinone) as the core material and gelatin (Gel) / gum arabic (GA) as the double-layer wall material, DCOIT microcapsules were prepared in two steps by complex coacervation and in-situ polymerization. In the first step, in the presence of GA, an inner shell was formed by complex coacervation of gelatin. Since the hydrophilic Gel has good film-forming properties, the Gel-GA inner layer has low permeability to DCOIT. In the second step, a polyurea-formaldehyde resin PUF outer layer (such as PUF) was deposited on the Gel-GA shell under acidic conditions through in-situ polymerization between urea-formaldehyde prepolymer and Gel-GA. Figure 4 Flow chart shown), to ensure that the double-walled microcapsules have high storage stability, sufficient mechanical properties and low permeation energy.

[0006] 2. Preparation of sodium alginate / chitosan composite gel spheres by ion gel method (Zhang Xiaojuan, Zhao Qingyun, Kang Minyan, et al. Preparation of sodium alginate / chitosan composite gel spheres and study of their adsorption performance for Pb~(2+) [J]. Chemical Engineer, 2024, 38(06): 12-16+27. DOI: 10.16247 / j.cnki.23-1171 / tq.20240612.), the specific method is:

[0007] Dissolve sodium alginate powder in ultrapure water to prepare sodium alginate solution, and let it stand. Weigh CaCl2 and stir and dissolve it in 1% acetic acid solution to prepare CaCl2 solution, then weigh chitosan (CS) and add it to the CaCl2 solution and stir evenly, drop the sodium alginate solution into the solution to prepare SA / CS composite gel balls, and crosslink for 1 hour. Rinse the SA / CS composite gel balls with ultrapure water several times. Place the SA / CS composite gel balls in a vacuum freeze dryer for drying to obtain freeze-dried SA / CS composite gel balls.

[0008] However, the maximum embedding rate of the microcapsules obtained by the above method 1 is less than 80%, and the maximum drug loading is less than 25%. The particle size of the microspheres obtained by the above method 2 can reach more than 2mm, the combined chitosan is small, and the sustained release effect is poor. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a method for preparing antifouling agent microspheres, the method comprising the following steps:

[0010] (1) mixing sodium alginate, copper pyrithione (CUPT) and CaCl2 solution for reaction, freeze-drying and then grinding to prepare intermediate product particles;

[0011] (2) mixing the intermediate product particles in step (1) with a chitosan (CS) solution for reaction, then adding a glutaraldehyde solution for further reaction, and freeze-drying to obtain the antifouling agent microspheres.

[0012] According to an embodiment of the present invention, in step (1), the mass ratio of sodium alginate to copper pyrithione is 1:1-1:5, preferably 1:1-1:3.

[0013] According to an embodiment of the present invention, in step (1), the concentration of the CaCl2 solution is 0.1-0.4M.

[0014] According to an embodiment of the present invention, in step (1), the mass ratio of copper pyrithione to CaCl2 is 1:2-1:7, for example, 1:4.

[0015] According to an embodiment of the present invention, in step (1), the sodium alginate is added in the form of a sodium alginate solution. Preferably, the concentration of the sodium alginate solution is 1-4wt%, for example, 1wt%, 2wt%, 2.5wt%, 3wt% or 4wt%.

[0016] According to an embodiment of the present invention, in step (1), the sodium alginate solution is first mixed with copper pyrithione to form a suspension, and then the suspension is added dropwise to a CaCl2 solution for reaction.

[0017] Preferably, the suspension is added dropwise by a syringe pump device at a dropping speed of 0.3-0.6 mL / min.

[0018] According to an embodiment of the present invention, in step (1), the temperature of the mixed reaction is 20°C-35°C, for example 25°C; and the reaction time is 1-3h, for example 1h.

[0019] According to an embodiment of the present invention, step (1) uses a grinder to grind and pulverize.

[0020] According to an embodiment of the present invention, in step (1), the particle size of the intermediate product particles is less than 100 um.

[0021] According to an embodiment of the present invention, in step (2), the concentration of the chitosan solution is 1-4 wt%, preferably 1-2 wt%.

[0022] According to an embodiment of the present invention, in step (2), the mass ratio of the intermediate product particles to chitosan (CS) is 1:1-1:5, preferably 1:1-1:3, for example 1:1.

[0023] According to an embodiment of the present invention, in step (2), the temperature for reacting the intermediate product particles with the chitosan solution is 20° C.-35° C., for example, 25° C.; and the reaction time is 1-4 h.

[0024] According to an embodiment of the present invention, in step (2), the reaction temperature after adding the glutaraldehyde solution is 50-80°C, and the reaction time is 0.5-4h.

[0025] According to an embodiment of the present invention, in step (2), the concentration of the glutaraldehyde solution is 1-4wt%, for example, 1wt%, 2wt%, 2.5wt%, 3wt% or 4wt%.

[0026] According to an embodiment of the present invention, in step (2), the freeze-drying time is 6-48 hours.

[0027] According to an embodiment of the present invention, in step (2), the antifouling agent microspheres are spherical.

[0028] According to an embodiment of the present invention, in step (2), the particle size of the antifouling agent microspheres is less than 100 um, for example, 1 um-100 um.

[0029] The invention also provides antifouling agent microspheres prepared by the method.

[0030] According to an embodiment of the present invention, the antifouling agent microspheres include copper pyrithione, sodium alginate and chitosan, wherein the sodium alginate is coated on the outer layer of the copper pyrithione, and the chitosan is coated on the outer layer of the sodium alginate; and the chitosan is covalently linked to glutaraldehyde.

[0031] The present invention also provides application of the antifouling agent microspheres in marine antifouling.

[0032] The principle of the present invention is as follows: in the first step, when a suspension of sodium alginate (SA) and CUPT is added to a CaCl2 solution, since SA molecules contain a large number of carboxyl groups, when divalent calcium ions are added to the SA aqueous solution, the Na of SA will be exchanged with the calcium ions, and the SA solution will then transform into a gel, that is, the glucuronic acid will fold and accumulate toward the cations, and then the stretched molecular chains will transform into an ordered band structure, and finally an egg core model gel with a three-dimensional molecular network will be formed, and the sodium alginate and calcium ions will be rapidly cross-linked to embed the CUPT into the sodium alginate.

[0033] In the second step, sodium alginate contains anionic groups that can be cross-linked with the cationic groups on the surface of chitosan: CS molecular chains contain a large number of active amino groups, and SA contains carboxyl groups. When SA gel microspheres are added to the acetic acid solution of CS, the COO- groups on the surface of the microspheres are exposed due to the acidic solution. 4+ Electrostatic cross-linking forms a hydrogel network.

[0034] In the third step, a nucleophilic addition reaction occurs between glutaraldehyde and amino groups, and chitosan and glutaraldehyde are cross-linked and solidified to form stable antifouling agent microspheres.

[0035] Beneficial effects of the present invention:

[0036] (1) The method of the present invention adopts a syringe pump to inject the CaCl2 solution, and the intermediate product particles obtained have uniform particle size, small particle size and good morphology.

[0037] (2) The raw materials used in the method of the present invention are environmentally friendly, safe, pollution-free and environmentally friendly.

[0038] (3) The method of the present invention can prepare antifouling agent microspheres with complete morphology, and the particle size is uniform and controlled below 100um. The use of copper pyrithione as an antifouling agent has more stable chemical properties. The sodium alginate used is a stabilizer that can wrap the antifouling agent copper pyrithione, reduce the release rate of copper ions, achieve a sustained release effect, extend the antifouling time of the antifouling agent copper pyrithione, maintain the long-term release of the antifouling agent, and help reduce the amount of antifouling agent, which can protect the environment to a certain extent; adding chitosan, a temperature-responsive material, makes the material have a certain temperature-sensitive responsiveness, and can show different release characteristics in different seawater temperatures to achieve a temperature control effect; the preparation process is simple to operate, the product has a high embedding rate, and has broad application prospects.

[0039] (4) In the antifouling agent microspheres of the present invention, the embedding rate can reach more than 90% (measured by elemental analysis), and the drug loading can reach a maximum of 80%, and the embedding efficiency is higher. The embedding rate refers to the ratio of the amount of copper pyrithione embedded in the antifouling agent microspheres to the total amount of copper pyrithione. The drug loading refers to the coating rate of sodium alginate on copper pyrithione.

[0040] (5) The preparation method of double cross-linking of sodium alginate and chitosan adopted in the present invention is relatively novel. By means of the cross-linking effect between sodium alginate and calcium ions and the electrostatic interaction between the anions and cations of sodium alginate and chitosan, a double-layer drug-carrying structure is constructed, which is a novel idea.

[0041] (6) The microspheres made of sodium alginate as a matrix in the present invention have an obvious sustained-release effect, and the chitosan added subsequently has a certain temperature sensitivity, so that the microsphere material has different release characteristics at low temperature and room temperature.

[0042] (7) The microspheres prepared by the method of the present invention have uniform morphology, complete spherical shape, and the particle size can be controlled below 100 μm. The embedding rate is high and the yield is large, which is suitable for actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a SEM image of the antifouling agent microspheres of Example 1.

[0044] Figure 2 The antifouling agent microspheres prepared in Examples 1-2 and Comparative Example 1 were tested for sustained release properties at 4° C. and 20° C., respectively.

[0045] Figure 3 It is a comparison chart of the copper ion release of the coating with copper pyrithione added in Test Example 2 and the microsphere coating containing Example 1 within 15 days.

[0046] Figure 4 The following is a flow chart of a prior art product. DETAILED DESCRIPTION

[0047] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0049] Example 1

[0050] 1. Add copper pyrithione (CUPT) to a 1.5% sodium alginate solution at a mass ratio of sodium alginate to copper pyrithione (CUPT) = 1:1, and perform ultrasound for 10 minutes to make the suspension uniform.

[0051] 2. The suspension was injected into 0.2M CaCl2 solution at a speed of 0.5ml / min through a syringe pump device for 60min, mixed and reacted at a temperature of 25°C for 60min, and the obtained microspheres were filtered. After freeze drying, they were crushed with a grinder and passed through a 150-mesh sieve. The sieved microsphere particles were subjected to the next step of reaction.

[0052] 3. The microsphere particles obtained in step 2 are added to a 1% mass fraction CS solution (solid content ratio, microsphere particles: CS = 1:1) for ion crosslinking at 25°C for 2 hours, then filtered and added to a 2.5% glutaraldehyde solution, allowed to stand for 1 hour, and finally heated to 70°C for reaction for 0.5 hours. Finally, the obtained beads are washed with distilled water and freeze-dried for 24 hours to obtain sodium alginate microspheres (i.e., antifouling agent microspheres) with chitosan coated on the surface and embedded with copper pyridinethione.

[0053] Figure 1 is a SEM image of the antifouling agent microspheres of Example 1, Figure 1 It can be proved that the antifouling agent microspheres are spherical, have good morphology, and the particle size distribution is in the range of 1um-100um.

[0054] The content of sulfur, a characteristic element of CPT, in the microspheres obtained in Example 1 was tested by an element analyzer. The results were repeated three times and were 9.86%, 10.05% and 9.39%, respectively, with an average content of 9.77%. The element content analysis showed that the embedding rate of the microspheres for the antifouling agent CPT was as high as 96.37%, and the drug loading rate of the microspheres was 48.19%.

[0055] Example 2

[0056] The difference between Example 2 and Example 1 is that in step 3 of Example 2, the concentration of the chitosan solution is 2 wt %.

[0057] Comparative Example 1

[0058] The difference between Comparative Example 1 and Example 1 is that chitosan is not added in Comparative Example 1.

[0059] Test Example 1

[0060] The antifouling agent microspheres prepared in Examples 1-2 and Comparative Example 1 were tested for sustained release properties at 4° C. and 20° C., respectively. The specific test method is as follows:

[0061] The antifouling agent microspheres prepared in Examples 1-2 and Comparative Example 1 were placed in 300 ml of 4°C or 20°C deionized water, and the release curves of copper ions within 24 hours were tested. The release curves of copper ions over time were obtained by ICP-MS, and the test results are as follows: Figure 2 As shown:

[0062] Figure 2 In the figure, SC refers to the test curve of Comparative Example 1, SCC-1 refers to the test curve of Example 1, and SCC-2 refers to the test curve of Example 2. Figure 2 It can be seen that the higher the chitosan concentration, the thicker the shell. The release rate and cumulative release amount are quite different. The release rates of the three materials at 20°C are higher than those of the same materials at 4°C. The antifouling agent microspheres SCC-1 and SCC-2 of the present invention have lower release amounts than SC without chitosan coating (i.e., comparative example 1) at the same temperature. The thicker the chitosan shell, the lower the concentration of released copper ions. This shows that the antifouling agent microspheres prepared by the method of the present invention have better temperature-controlled release performance.

[0063] Test Example 2

[0064] Weigh 0.05 g of copper pyrithione CUPT and the antifouling agent microspheres prepared in Example 1 (i.e. Figure 3 SA-CUPT) 0.1g, at this time the copper content of the two is equal, added to 1ml polyurethane matrix, stirred evenly with a magnetic stirrer, and then applied to a 7*7cm PVC board. Cured at room temperature for 24 hours to obtain two composite coatings. The cumulative release of Cu ions was measured by ICP-MS within 15 days. The test results are as follows Figure 3 As shown, from Figure 3 It can be seen that the release amount increases slowly within 15 days, and the cumulative release amount of directly adding CUPT into the coating is significantly higher than that of the microspheres, indicating that the antifouling agent microspheres prepared by the present invention have good sustained release performance.

[0065] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing antifouling agent microspheres, characterized in that: The method comprises the following steps: (1) mixing sodium alginate, copper pyrithione and CaCl2 solution for reaction, freeze-drying and then grinding to prepare intermediate product particles; (2) mixing the intermediate product particles in step (1) with a chitosan solution for reaction, then adding a glutaraldehyde solution for further reaction, and freeze-drying to obtain the antifouling agent microspheres.

2. The method according to claim 1, characterized in that In step (1), the mass ratio of sodium alginate to copper pyrithione is 1:1-1:

5. Preferably, in step (1), the concentration of the CaCl2 solution is 0.1-0.4M.

3. The method according to claim 1 or 2, characterized in that: In step (1), the mass ratio of copper pyrithione to CaCl2 is 1:2-1:

7. Preferably, in step (1), the sodium alginate is added in the form of a sodium alginate solution. Preferably, the concentration of the sodium alginate solution is 1-4 wt%.

4. The method according to any one of claims 1 to 3, characterized in that: In step (1), the temperature of the mixed reaction is 20°C-35°C; and the reaction time is 1-3h. Preferably, in step (1), the particle size of the intermediate product particles is less than 100 um.

5. The method according to any one of claims 1 to 4, characterized in that: In step (2), the concentration of the chitosan solution is 1-4wt%. Preferably, in step (2), the mass ratio of the intermediate product particles to chitosan is 1:1-1:

5. Preferably, in step (2), the temperature for reacting the intermediate product particles with the chitosan solution is 20° C.-35° C., and the reaction time is 1-4 h. Preferably, in step (2), after adding the glutaraldehyde solution, the reaction temperature is 50-80° C., and the reaction time is 0.5-4 h.

6. The method according to any one of claims 1 to 5, characterized in that: In step (2), the concentration of the glutaraldehyde solution is 1-4wt%.

7. The method according to any one of claims 1 to 6, characterized in that: In step (2), the antifouling agent microspheres are spherical. Preferably, in step (2), the particle size of the antifouling agent microspheres is less than 100 um.

8. Antifouling agent microspheres prepared by the method according to any one of claims 1 to 7.

9. The microsphere according to any one of claims 1 to 6, characterized in that: The antifouling agent microspheres comprise copper pyrithione, sodium alginate and chitosan, wherein the sodium alginate is coated on the outer layer of the copper pyrithione, and the chitosan is coated on the outer layer of the sodium alginate; and the chitosan is covalently linked with glutaraldehyde.

10. Use of the antifouling agent microspheres according to claim 8 or 9 in marine antifouling.

Citation Information

Patent Citations

  • Method for preparing nano MgO sustained-release sterilizing granules

    CN102428961A

  • Preparation process for thermosensitive controlled-release material for marine antifouling agent

    CN102726382A

  • VEGF and vancomycin-supported multilayer slow release microsphere preparation, and preparation method and application thereof

    CN104147594A

  • Preparation method of chitosan / sodium alginate magnetic composite microsphere capable of adsorbing heavy metal ions

    CN106984290A

  • Method for preparing 5-fluorouracil delivery microspheres

    CN107823177A

Cited By

  • Compositions and methods for antifouling protection

    WO2026122484A1